Сокровище призраков: [роман] / Мария Жукова-Гладкова - Жукова-Гладкова Мария (Двойной крутой детектив, 2012)
Экземпляры: абонемент (20180212) / Инвентарный номер: / Цена: [50.00] / Сис.шифр: 84(2Рос-Рус)6 / Авт.знак: Ж 86 / ГРНТИ: 17.82.31 / ББК: 84(2 РОС=Рус)6